Liquid phase adsorption isotherm of nonyl phenol on activated carbon - Awang Bono; Chu, Chi Ming; Phong, Ming San (Penerbit UMS, 2002)
In this work, the excess adsorption isotherm of nonyl phenol was measured by a combination of conventional techniques but analysed by using Langmuirian-type monolayer adsorption theory. The results showed that the excess isotherm obeyed the Langmurian type monolayer theory and the individual equilibrium adsorption is well represented by Langmuirian type of adsorption.